الميزانية وفق متطلبات المعيار الدولي رقم 12 في الجزائر - هيثم, بدرة; نضال, طريلي; يونس, الأطرش; نصر الدين, بشيري (University of eloued جامعة الوادي, 2022)
"النظام المحاسبي المالي هو نظام لتنظيم المعلومة المالية يسمح بتخزين معطيات قاعدية عددية تصنيفها وتقييمهاو تسجيلها و عرض كشوف تعكس صورة صادقة عن الوضعية المالية و ممتلكات الكيان و وضعية خزينته في نهاية السنة المالية الميزانية الجبائية الذي يقوم على أساسه إعداد القوائم المالية يخدم التحليل المالي للقوائم المالية ويسهل من تطبيق تقنيات التحليل المالي حيث تهدف هذه القوائم حسب الجريدة الرسمية إلى تقديم المعلومات حول الوضعية المالية الميزانية و الاداء و حساب النتائج وهو يتوافق مع أهداف التحليل المالي للقوائم المالية ""The financial accounting system is a system for organizing financial information that allows storing, categorizing, evaluating, and recording numerical base data, and displaying statements that reflect a true picture of the financial position, the entity's property and the position of its treasury at the end of the fiscal year . The fiscal budget, on the basis of which the preparation of the financial statements is based, serves the financial analysis of the financial statements and facilities the application of financial analysis techniques . These statements, according to the official Gazette, aim to provide information about the financial position ""budget"" ,performance ""calculation of results"" and it's consistent with .The objectives of the analysis financial statements for the financial statements"
ماستر محاسبة
Keywords: الميزانية الجبائية،المعيار الدولي رقم 12; fiscal budget,International Standard No. 12